Land use in permanent preservation areas of grande river (MG) - de Oliveira, Carlos Delano Cardoso [UNESP]; Borges, Luís Antônio Coimbra; Júnior, Fausto Weimar Acerbi (FapUNIFESP (SciELO), 2018)
The Brazilian Forestry Code established the Permanent Preservation Areas (PPAs) to preserve environmentally significant areas, such as the banks of waterways. Grande River is an important Brazilian river whose watercourse contains several hydroelectric plants, with few PPAs containing original features. Thus, this study analyzed land use in PPAs of a non-dammed stretch of the upper Rio Grande, in southern Minas Gerais. For this analysis, we used an image of the Rapideye sensor and the Maximum Likelihood classification method. The results showed the occurrence of pastures (49.63%), exposed soil (9.13%), others (0.77%), water (0.15%) and ornamental vegetation (0.13%) while the remaining native vegetation represented only 40.19% of PPAs. These numbers show that environmental laws have not been fulfilled in this area and there is strong human intervention in the PPAs studied.
Keywords: Brazilian Forestry Code; Geoprocessing; Land occupation